ISLAMIC COMMERCIAL BANKS AND SHARIA BUSINESS UNITS; HOW EFFICIENT ARE THEY? - Indra Kusuma, Septian; Dorkas Rambu Atahau, Apriani (LPPM Universitas Terbuka, 2019)
The purpose of this study is to determine the efficiency level of Islamic commercial banks and Sharia Business Units for the period of 2012-2017 and to examine the existence of size effect in bank efficiency. Using Data Envelopment Analysis (DEA) method, this research employs total assets, deposits, and operating costs as the inputs, while the output is total financing and operating income. The samples are 11 Islamic commercial Banks and 20 Sharia Business Units. Results of this study show that Islamic commercial banks are more efficient than Sharia Business Units during the period of analysis and large Islamic commercial banks are more efficient than small sharia business units which provide evidence of size effect existence in bank efficiency. Thus, the policymaker needs to consider bank size in policy formulation regarding bank efficiency.